San Martino in Soverzano, da insediamento fortificato a villa rinascimentale - Ceccarelli, Francesco (Opus Incertum, 2016)
Some of the most important country residences of the Bolognese nobility, which can be found in the area between Bologna, theriver Reno and the province of Ferrara, often evolved in the 15th century from previous small fortified settlements. In EgnazioDanti’s book of drawings, which he produced in 1578 for what was later to become the Gallery of Maps of the Vatican, what isstriking is the permanence of the fortified nature of the settlements, something that had, however, already been considered asindispensable for life in a villa by Pier de’ Crescenzi in the early 14th century. The disappearance of many of the buildings hasnot allowed as yet the writing of a satisfactory history of the original pre-renaissance villa settlements, nor the carrying out of aproper census of them in the region. From this point of view, the complex at San Martino in Soverzano represents a particularlysignificant case for establishing a first well-documented interpretative framework on the phenomenon of pre-renaissance countrymanors in the province of Bologna.